SAPHO syndrome: the supposed trigger by isotretinoin, the efficacy of adalimumab and the specter of depressive disorder: a case report - Michele Luzzati; Gabriele Simonini; Cesare Filippeschi; Teresa Giani; Sandra Trapani (BMC, 2020)
Abstract Background SAPHO (synovitis, acne, pustolosis, hyperostosis and osteitis) syndrome is a rare autoinflammatory chronic disorder, presenting with non-infectious osteitis, sterile joint inflammation and skin manifestations including palmoplantar pustolosis and severe acne. It could be often misdiagnosed for its heterogeneous clinical presentation. Treatment is challenging and, due to the rarity of this syndrome, no randomized controlled clinical trials have been conducted. Empirical treatments, including non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, antibiotics and bisphosphonates and disease-modifying anti-rheumatic drugs (DMARDs) could be quite effective. Anti-tumor necrosis factor-alpha (anti-TNF-α) agents and interleukin-1 (IL-1) antagonists have shown promising results in refractory patients. Isotretinoin, commonly used for severe acne, has been rarely described as possible trigger of osteo-articular manifestations, in particular sacroiliitis. Case presentation The case of a boy, affected by acne fulminans and depression, who presented with sacroiliitis after a 10-week treatment with isotretinoin is presented. After SAPHO diagnosis, NSAIDs therapy was started but the onset of bilateral gluteal hidradenitis suppurativa required the switch to a TNF-α antagonist (Adalimumab) with the achievement of a good control of the disease. Despite specific therapy with sertraline, the patient continued to complains severe depression. Conclusions Our case reports a temporal association between the onset of osteo-articular symptoms and the introduction of isotretinoin, as previously described. However, this timeline is not sufficient to establish a causal role of this drug into the pathogenesis of sacroiliitis. At this regard, further studies are required. The occurrence of hidradenitis suppurativa during SAPHO course supported the introduction of TNF-α blockers with a favourable result, as reported in a few cases in literature. The association between SAPHO syndrome and depressive mood disorders is already reported. Our patient experienced severe depression whose trend seems to be independent from the course of the main disease. Currently, it is not clarified if depression could be considered reactive to the underling disease or if it forms an integral part of the autoinflammatory disorder.